A compliant control method for robust trot motion of hydraulic actuated quadruped robot. (22nd November 2018) - Chen, Teng; Rong, Xuewen; Li, Yibin; Ding, Chao; Chai, Hui; Zhou, Lelai
A motion control approach is proposed for hydraulic actuated quadruped robots, aiming to achieve active compliance and robust motion control. The approach is designed with a structure of three layers. Servo valve-controlled asymmetric hydraulic cylinder model is established to obtain the relationship between the desired torque and the control current signal, which is the bottom layer. The middle layer is based on the virtual model of the leg for active compliance. The upper layer considers the torso posture and velocity into planning the foot trajectories based on the spring loaded inverted pendulum model. Trotting gait simulations are conducted based on the proposed framework in the simulation software environment Webots. The motion control approach has been implemented on a robot prototype SCalf-II (SDU calf), where experiments have been conducted including omnidirectional trotting gait, lateral impact recovery and climbing slopes. The experiments demonstrate that the proposed approach can effectively control the hydraulic actuated robots.